2019
DOI: 10.3390/ijerph16152652
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Quality of Life in Individuals with Type 2 Diabetes Mellitus Is Associated with Emotional Distress

Abstract: Background: individuals with type 2 diabetes show emotional distress as they learn how to cope with the disease. The emotional distress increases the possibility of complications in these patients. The aims of the present study were to evaluate the impact of the emotional distress in the quality of life of individuals with diabetes, and to investigate the demographic and clinical characteristics associated with the emotional distress of living with diabetes in a Mexican population. Methods: a total of 422 Mexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
2
15
0
5
Order By: Relevance
“…To assess the association of study variables with the presence of mental disorders, psychological distress, and consumption of psychiatric medications among DM cases, we constructed three unconditional logistic regressions following Hosmer et al’s recommendation [ 29 ]. We included in the multivariable models all the independent variables with significant bivariate associations ( p < 0.10), with the dependent variable and those considered scientifically relevant in other investigations [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 14 , 20 ]. In order to fit the multivariable model, the importance of each variable was verified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the association of study variables with the presence of mental disorders, psychological distress, and consumption of psychiatric medications among DM cases, we constructed three unconditional logistic regressions following Hosmer et al’s recommendation [ 29 ]. We included in the multivariable models all the independent variables with significant bivariate associations ( p < 0.10), with the dependent variable and those considered scientifically relevant in other investigations [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 14 , 20 ]. In order to fit the multivariable model, the importance of each variable was verified.…”
Section: Methodsmentioning
confidence: 99%
“…Psychological distress is frequently found in people who experience DM and has been associated with adverse health outcomes and unhealthier behaviors [ 10 , 11 ]. Gomez-Pimienta et al [ 12 ] found that around 32% of patients with DM presented high diabetes-related emotional distress and had a decreased quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Emotion‐related diabetes distress is also common in patients with diabetes 1,19 and has been linked to depressive symptoms 2,20 which, in turn, can contribute to decreased physical and mental quality of life 21 . High diabetes emotional distress is associated with decreased quality of life, 22 whereas good psychosocial well‐being is a predictor of better quality of life 16 . Depression in patients with diabetes has also been found to negatively impact the various domains of quality of life 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also looked at the key factors in stroke and diabetes mellitus of the aged in Taiwan [ 15 , 16 ]. Some research also discussed the effects of chronic disease, physical functions, and lifestyles of the middle-aged, and health changes of aged people [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Chiu et al [ 26 ] discussed the correlation between BMI (Body Mass Index) changes and diabetes mellitus of the aged in Taiwan.…”
Section: Introductionmentioning
confidence: 99%